A comparative study of three drying methods on drying time and physicochemical properties of chicken powder. Issue 3 (17th February 2019) - Ran, Xin-Li; Zhang, Min; Wang, Yuchuan; Liu, Yaping
ABSTRACT: Chicken powder produced by hot air drying (HAD), hot air-assisted radio frequency drying (HA-RFD) and spray drying (SD) was obtained. Drying time along with flavor, taste, free amino acid (FAA) content and physico-chemical properties of products were compared. It was resulted that HA-RFD was the fastest means (90 min) with HAD was the slowest (240 min) to achieve target moisture content (under 5%). Concerning product quality, HA-RFD chicken powder exhibited the lowest hygroscopicity (1.80%), best rehydration (137.72%), and better flavor and taste as well as color, and HAD powder exerted best color, solubleness (45.68%) and better rehydration (130.27%). While for chicken powder produced by SD showed the most undesirable color and flavor and highest degree of hygroscopicity (8.40%). Besides, the total FAA content of HA-RFD was the most abundant (3.615 g/100 g), followed by HAD (3.551 g/100 g) and the SD powder had minimum content of total FAA (1.175 g/100 g), which suggested that HA-RFD can reduce thermal quality degradation and improve nutritional value with the lowest damage. Besides, HA-RFD chicken powder had the largest total content of Asp and Glu (3.615 g/100 g), which were the primary contributor to umami. Based on the results, it was concluded that HAD or HA-RFD appeared to be a promising way to prepare for chicken powder.